Comparison of Robust Control Techniques for Use in Flight Simulator Motion Bases - Becerra-Vargas, Mauricio [UNESP]; IEEE (Ieee, 2015)
The purpose of this study is to analyse and compare three control strategies based on the inverse dynamics control structure for a six degree of freedom flight simulator motion base driven by electromechanical actuators. All strategies are applied in the outer loop of the inverse dynamic control structure by considering imperfect compensation of the nonlinearities. Imperfect compensation is intentionally introduced in order to simplify the implementation of the inverse dynamic control structure. The first strategy is just a proportional and derivative control, the second is based on Lyapunov stability theory and the third is based on H-Infinity theory. Acceleration step response and smoothness of the actuators driven torques were used to compare the performance of the controllers. The results are based on numerical simulations.
Keywords: Inverse Dynamics Control; H-Infinity Theory; Sliding Mode Control; Flight Simulator Motion Base; Stewart Platform; Parallel Robot